Tricyclic antidepressants, quinacrine and a novel, synthetic chimera thereof clear prions by destabilizing detergent-resistant membrane compartments - Löber, Stefan; Gmeiner, Peter; et al. (Journal of Neurochemistry, 2006)
Prion diseases are invariably fatal, neurodegenerative diseases transmitted by an infectious agent, PrPSc, a pathogenic, conformational isoform of the normal prion protein (PrPC). Heterocyclic compounds such as acridine derivatives like quinacrine abolish prion infectivity in a cell culture model of prion disease. Here, we report that these compounds execute their antiprion activity by redistributing cholesterol from the plasma membrane to intracellular compartments, thereby destabilizing membrane domains. Our findings are supported by the fact that structurally unrelated compounds with known cholesterol-redistributing effects - U18666A, amiodarone, and progesterone - also possessed high antiprion potency. We show that tricyclic antidepressants (e.g. desipramine), another class of heterocyclic compounds, displayed structure-dependent antiprion effects and enhanced the antiprion effects of quinacrine, allowing lower doses of both drugs to be used in combination. Treatment of ScN2a cells with quinacrine or desipramine induced different ultrastructural and morphological changes in endosomal compartments. We synthesized a novel drug from quinacrine and desipramine, termed quinpramine, that led to a fivefold increase in antiprion activity compared to quinacrine with an EC50 of 85 nM. Furthermore, simvastatin, an inhibitor of cholesterol biosynthesis, acted synergistically with both heterocyclic compounds to clear PrPSc. Our data suggest that a cocktail of drugs targeting the lipid metabolism that controls PrP conversion may be the most efficient in treating Creutzfeldt-Jakob disease. © 2006 The Authors.
UnivIS-Import:2015-03-09:Pub.2006.nat.dchph.lphch.tricyc
Keywords: Cholesterol; Creutzfedt-Jakob disease; Detergent-resistant membrane domains; Heterocyclic compounds; Prions; Tricyclic antidepressants